Comparing the reliability of muscle oxygen saturation with common performance and physiological markers across cycling exercise intensity - Yogev, A.; Arnold, J.; Nelson, H.; Clarke, D. C.; Guenette, J. A.; Sporer, B. C.; Koehle, M. (Frontiers in Sports and Active Living, 2023)
Introduction: Wearable near-infrared spectroscopy (NIRS) measurements of muscle oxygen saturation (SmO2) demonstrated good test-retest reliability at rest. We hypothesized SmO2 measured with the Moxy monitor at the vastus lateralis (VL) would demonstrate good reliability across intensities. For relative reliability, SmO2 will be lower than volume of oxygen consumption (VO2) and heart rate (HR), higher than concentration of blood lactate accumulation ([BLa]) and rating of perceived exertion (RPE). We aimed to estimate the reliability of SmO2 and common physiological measures across exercise intensities, as well as to quantify within-participant agreement between sessions.